2021
DOI: 10.1016/bs.aesp.2021.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The relational logic of moral inference

Abstract: How do we make inferences about the moral character of others? Here we review recent work on the cognitive mechanisms of moral inference and impression updating. We show that moral inference follows basic principles of Bayesian inference, but also departs from the standard Bayesian model in ways that may facilitate the maintenance of social relationships. Moral inference is not only sensitive to whether people make moral decisions, but also to features of decisions that reveal their suitability as a relational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 250 publications
1
6
0
Order By: Relevance
“…A potential process is that interdependent individuals boost a friendly first impression (Meng et al, 2022) and try to sustain it in the presence of inconsistent information, and are thus more willing to help others. Our research provides support for the proposition that responding to negative behaviors with leniency is adaptive for healthy social functioning (Crockett et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A potential process is that interdependent individuals boost a friendly first impression (Meng et al, 2022) and try to sustain it in the presence of inconsistent information, and are thus more willing to help others. Our research provides support for the proposition that responding to negative behaviors with leniency is adaptive for healthy social functioning (Crockett et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…The findings of study 2 were consistent with those of study 1, as the IIDI was negatively correlated with the negative index of updating. That is, in both the interaction-based paradigm and the description-based paradigm, the motivation to maintain relationships affects impression updating, supporting the relational logic in moral inference from the perspective of individual differences (Crockett et al, 2021). However, it is worth noting that there were some differences between the two studies.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This result held even for more nationalistic participants—consistent with previous evidence for a disconnect between participants’ own preferences in moral dilemmas and what kind of person they trust (Everett et al, 2016, 2018, 2021). That is, even when participants recognize that a redistributive policy is less beneficial for themselves, they can still trust a person in power who endorses that policy—potentially because this can signal an impartial commitment to the greater good (Crockett et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study also contributes to the person perception literature on moral character. Prior studies have shown that people automatically and effortlessly evaluate others’ moral character, and that these evaluations play a crucial role in determining our overall positive or negative evaluations of others (Brambilla, Sacchi, Rusconi, & Goodwin, 2021; Critcher, Helzer, & Tannenbaum, 2020; Crockett, Everett, Gill, & Siegel, 2021; Goodwin et al, 2014; Uhlmann, Pizarro, & Diermeier, 2015). Our study extends prior work by focusing on a consequence of moral character evaluations.…”
mentioning
confidence: 99%